Correction: Fmoc-diphenylalanine hydrogels: understanding the variability in reported mechanical properties. Issue 44 (7th November 2022) - Raeburn, Jaclyn; Pont, Guillaume; Chen, Lin; Cesbron, Yann; Lévy, Raphaël; Adams, Dave J.
Abstract : Correction for 'Fmoc-diphenylalanine hydrogels: understanding the variability in reported mechanical properties' by Jaclyn Raeburn et al., Soft Matter, 2012, 8, 1168–1174, ; https://doi.org/10.1039/C1SM06929B .